Health impact assessment of a voluntary protocol to decrease salt in bread: what can we learn?. (20th October 2021) - Costa, L; Santos, J; Alves, J; Braz, P; Brazão, R; Costa, A; Santos, M; Assunção, R; Caldas de Almeida, T
Abstract: Issue: Hypertension (HT) is a major and modifiable risk factor for cardiovascular diseases (CVD), which can be caused by excessive salt intake. Portugal has one of the highest mortality rate due to CVD in Europe, mainly due to HT. Thus, reduction of salt intake from food products is one of major strategies advocated to modify blood pressure (BP) and its impact on HT. Description of the problem: The Portuguese population has excessive daily salt intake mainly due to bread consumption. Thus, in 2017 a voluntary 'Protocol' was signed between stakeholders with the goal to reduce salt content in bread by 2021. Herein, using a Health Impact Assessment (HIA) approach we aimed to estimate the potential effect in BP from the implementation of this 'Protocol'. Thus, two national surveys were used to find average values of salt intake and BP on population, while estimates of BP reduction were calculated based upon meta-analysis data. Results: It was expected that the implementation of the 'Protocol' could reduce salt ingestion and have a higher BP effect, mostly in more vulnerable populations. In fact, results showed that individuals with low educational level, men, aged and residents in the South region of Portugal were the ones that could more benefit from the 'Protocol' implementation. However, this study found that the effects were be very low for all groups analysed, suggesting that only slight health gains can occur. Lessons: The 'Protocol' as a voluntary agreement is not sufficient to attain the public health targets devised. Following the HIA framework, further complementary and intersectoral integrated measures, through the use of compulsory food and fiscal policies preferably extended to other highly consumed food products, were thus recommended. HIA could be used as a comprehensive tool to assess health impacts, supporting at each national context the design and implementation of effective strategies to promote salt intake reduction and effectively prevent hypertension. Key messages: The systematic use of HIA to design the appropriate policy framework and to inform adequately political decision-making is crucial to promote health and prevent Non-Communicable Diseases. Voluntary agreements should be complemented by other integrated measures to improve the efficacy of policies aiming to reduce salt intake and prevent hypertension.